2018
DOI: 10.1016/j.dib.2018.01.058
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing data of Notch ligand treated human dental pulp cells

Abstract: Indirect immobilized ligand has been shown as an effective technique to activate Notch signalling in vitro. The data presented in this article are related to the published article entitled “Indirect immobilized Jagged1 suppresses cell cycle progression and induces odonto/osteogenic differentiation in human dental pulp cells” (Manokawinchoke et al. 2017) [1]. This data article describes gene expression in indirect immobilized Jagged1 treated human dental pulp cells (hDPs) using high throughput RNA sequencing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Further, the decrease expression of mRNA related to cell cycle was observed in Jagged1‐treated hPDLs compared with the control. Similarly, Jagged1‐treated human dental pulp cells (hDPs) also enhanced genes related to extracellular matrix pathway and attenuated genes involving in cell cycle regulation (Manokawinchoke, Nattasit et al, ; Manokawinchoke et al, ). The present study demonstrated that CDK1 and PLK1 were downregulated in Jagged1‐treated hPDLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the decrease expression of mRNA related to cell cycle was observed in Jagged1‐treated hPDLs compared with the control. Similarly, Jagged1‐treated human dental pulp cells (hDPs) also enhanced genes related to extracellular matrix pathway and attenuated genes involving in cell cycle regulation (Manokawinchoke, Nattasit et al, ; Manokawinchoke et al, ). The present study demonstrated that CDK1 and PLK1 were downregulated in Jagged1‐treated hPDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, tissue culture surfaces were incubated with recombinant protein G at a concentration of 50 μg/ml for 16 hr. After washing, surfaces were then incubated with bovine serum albumin (10 mg/ml) for 2 hr and Jagged1/Fc (10 nM) for 2 hr, respectively (Beckstead et al, ; Manokawinchoke, Nattasit et al, ; Manokawinchoke et al, ; Osathanon, Ritprajak et al, ). Human IgG Fc fragment (hFc) was employed in the control condition.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was evaluated using MTT assay. 46 We used a standard cell line toxicity test to appreciate the cell viability. In this assay, we maintained a mouse fibroblast cell line L929 in DMEM (Sigma-Aldrich) containing 10% FBS, l -glutamine, penicillin, and streptomycin at 37 °C in humidified air containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was evaluated using MTT assay . We used a standard cell line toxicity test to appreciate the cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…Immobilized Jagged1-treated human dental pulp cells (hDPCs) exhibited the upregulation of genes that are involved in ECM components as well as ECM-receptor interaction and focal adhesion-related pathways, such as ECM organization, collagen biosynthesis, and modification of enzymes (Manokawinchoke et al, 2017). In addition, Jagged1 plays a pivotal role in the cell-matrix interaction (Nehring et al, 2005).…”
Section: Introductionmentioning
confidence: 99%